A spontaneous point mutation in the single 23S rRNA gene of the thermophilic arachaeon Sulfolobus acidocaldarius confers multiple drug resistance. - Aagaard, C (1994)
Development of transformable vectors for thermophilic archaea requires the characterization of appropriate selectable marker genes. Many antibiotic inhibitors of protein biosynthesis are known to bind to rRNA; therefore, we screened 14 for their capacity to inhibit growth of the thermophilic archaeon Sulfolobus acidocaldarius. Carbomycin, celesticetin, chloramphenicol, puromycin, sparsomycin, tetracycline, and thiostrepton all inhibited growth by different degrees. Spontaneous drug-resistant mutants were isolated from plates containing celesticetin or chloramphenicol. Six mutants from each plate exhibited a C-2585-to-U transition in the peptidyl transferase loop of 23S rRNA (corresponding to C-2452 in Escherichia coli 23S rRNA). The single-site mutation also conferred resistance to carbomycin. The mutated 23S rRNA gene provides a potentially useful and dominant marker for a thermophilic archael vector.